PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN MINAT BELAJAR TERHADAP MATERI BILANGAN BULAT PADA PESERTA DIDIK KELAS IV SDI HABI - Asang, Sandry Patricia Glory (Journal of Mandalika Literature, 2023)
This study aims to find out the effect of applying the Index Card Match Learning Model in Increasing Student Learning Interest in Integer Material. This research was conducted at SD Inpres Habi Class IV. This study uses qualitative research with a survey method that takes samples from a number of populations and uses a questionnaire as a means of collecting data. The population in this study amounted to 17 students who were all studied. The sampling technique in this study used saturated sampling or sensus sampling, where all members of the population were sampled. This research is Classroom Action Research which is carried out in repeated cycles, where each cycle consists of a series of four activities namely, action planning, action implementation, observation (evaluation), and reflection. Based on the frequency distribution on predetermined criteria regarding students' learning interest in learning mathematics using the Index Card Match model, it shows that 13 students answered in the High category. Therefore, the results of this study concluded that the application of the index card match learning model can increase the learning interest of fourth grade students in integer material at SDI Habi.